From Groningen to Pafos: Ideas and reflections from one conference inspiring the next - Filipa Teixeira; Thomas Gültzow (European Health Psychologist, 2026)
This editorial introduces the second regular issue of The European Health Psychologist in 2026, published just ahead of the 40th Annual EHPS Conference in Pafos. Drawing inspiration from the 2025 conference in Groningen while looking forward to this year’s meeting, the issue brings together contributions exploring patient–provider communication, open science infrastructure, experiences of conference participation, and opportunities for early career researchers. Reflections from grant recipients and an online attendee offer complementary perspectives on the scientific, social, and inclusive dimensions of EHPS conferences, while practical advice on navigating conference programmes, networking, and social activities helps readers prepare for Pafos. The issue also previews CREATE activities planned for 2026. As EHPS celebrates four decades of annual conferences, we reflect on this year’s theme, “Digital Innovations in Health: Harnessing the Power of Technology and AI,” and the opportunities and challenges emerging technologies bring to health psychology, inviting these conversations to continue beyond Pafos and into future EHP contributions.